Penentuan Isoform Sitokrom P450 Potensial pada Metabolisme Obat dengan Model Obat Gliklazid - Suharjono (Pengurus Pusat Ikatan Apoteker Indonesia, 2006)
With the advancement of molecular biology techniques and extended use of human liver microsomes (HLM), we have known the specific isoform of cytocrome P450 (CYP450) involved in human drug metabolisms. The specific isoform need certain physicochemistry characteristic of the drug to be metabolized, e.g. log P, pKa, log D7.4, a/d2, l/w, SA, vol, E , ELUMO and μ , which theoriticaly can be measured from its chemical structure using COMPACT software. There are, at least, 8 human liver microsomal CYP450 isoforms involved in drug metabolism. In this experiment we use gliclazide as drug model which will be metabolized into 3 main metabolites; inhbitor will inhibit the formation of the 3 metabolites and can be calculated further the value of % inhibition. From the inhibitor concentration and the greatest % inhibition compare to control, we can predict the specific CYP450 isoform involved in the metabolism of drug model. From the results of the experiment we can conclude that CYP2C9 isoform is the potential CYP450 isoform involved in the formation of glicazide metabolites. There are suitable physicochemistry characteristic of the inhibitor sulfafenazol and the substrate glicazide with CYP450 isoform enzyme’s specificity.